Down Syndrome: functionality and therapeutic history of the child, adaptation and occupational performance of parents - Halberstadt, Bianca Fraga (2020)
The aim of this study is to analyze the functionality of children with DS in the areas of mobility, self-care and social function in relation to the child’s therapeutic history, parental adaptation, child’s disability, socioeconomic aspects and parents’ occupational performance. The Pediatric Disability Assessment Inventory, Canadian Occupational Performance Measure, the Parental Adaptation Scale for child’s disability and an interview constructed by the researchers were used. Thirty parents of children with DS from 10 months to seven years old participated. Children have mobility performance within the normal range and a significant delay in the area of self-care. The most therapies are structural in nature, focused on family and child. The parents’ occupational performance presents problems, mainly in the area of productivity. These have difficulty in dealing with the diagnosis. The socioeconomic level, schooling and leisure activities of the parents influence child’s development.